Bidirectional Control of Reversal in a Dual Action Task by Direct and Indirect Pathway Activation in the Dorsolateral Striatum in Mice - Laurent, Muriel; De Backer, Jean-François; Rial, Danie; Schiffmann, Serge N.; de Kerchove d'Exaerde, Alban (Frontiers in Behavioral Neuroscience, 2017)
The striatum is a key brain structure involved in the processing of cognitive flexibility, which results from the balance between the flexibility demanded for novel learning of motor actions and the inflexibility required to preserve previously learned actions. In particular, the dorsolateral portion of the striatum (DLS) is engaged in the learning of action sequence. This process is temporally driven by fine adjustments in the function of the two main neuronal populations of the striatum, known as the direct pathway medium spiny neurons (dMSNs) and indirect pathway medium spiny neurons (iMSNs). Here, using optogenetics, behavioural and electrophysiological tools, we addressed the relative role of both neuronal populations in the acquisition of a reversal dual action sequence in the DLS. While the channelrhodopsin-induced activation of dMSNs and iMSNs of the DLS did not induce changes in the learning rate of the sequence, the specific activation of the dMSNs of the DLS facilitated the acquisition of a reversal dual action sequence; the activation of iMSNs induced a significant deficit in the acquisition of the same task. Taken together our results indicate an antagonistic relationship between dMSNs and iMSNs on the acquisition of a reversal dual action sequence.